Performance of Common Down Syndrome Screening Methods Used in India with Construction of an Indian Normogram for Nuchal Translucency/Crown–Rump Length Measurements in 14,337 Subjects - Kaul, Anita (J Obstet Gynaecol India, 2019)
BACKGROUND/PURPOSE OF STUDY: Sonologists often lack access to the Fetal Medicine Foundation Down syndrome risk calculation software or cannot offer the combined test for aneuploidy screening because of resource constraints. Instead, sonologists use nuchal translucency (NT) measurements that rely on fixed NT cut-offs for labelling foetuses with high risks for Down syndrome. In the present study, we aimed to plot normative data for NT and the crown–rump length (CRL) in Indian foetuses and to assess the value of using the 95th/99th centiles of NT for CRL cut-offs instead of fixed NT cut-offs to calculate the risk for aneuploidies during the first trimester. METHODS: We conducted a retrospective observational study measuring the NT/CRL in 14,337 Indian foetuses between 11 and 13 + 6 weeks of gestation. We used regression analysis and calculated the 95th/99th centiles of NT distribution. We compared performances of NT > 95th/99th centiles and fixed NT cut-offs of 2.5- and 3.5-mm  as screening. RESULTS: The NT measurements increased with increasing CRL values. NT > 95th centile for a particular CRL for detecting all aneuploidies had the maximum sensitivity of 73.9% for a false positive rate (FPR) of 4.3%. Similar values for fixed cut-off > 2.5 mm were 63.0% FPR 3.7% (T21 68.2 FPR 3.8%) and for NT > 3.5 mm 36.9% FPR 0.43% (T21 36.5% FPR 0.5%) CONCLUSION: A fixed NT cut-off point is not appropriate for the first trimester screening. The best sensitivity for assessing aneuploidies is achieved using the 95th centile, but the 99th centile achieves higher specificity for gestational age. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13224-018-1196-3) contains supplementary material, which is available to authorized users.